Strategi Mewujudkan Ekowisata di Subak Intaran Barat, di Kecamatan Denpasar Selatan, Kota Denpasar - NI MADE MIA WULANDARI; I WAYAN WINDIA; I MADE SARJANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
Strategies for Realizing Ecotourism in the Subak of West Intaran of SouthDenpasar Sub-District, Denpasar City Institutional development is a very important component in the success of agriculturaldevelopment. Institutions that have an important role in agricultural development in Baliare the subak system. At the present day, Subak faces a serious challenge to maintain itsexistence. One of the concepts offered to overcome the problem of subak is throughintegrating agriculture with tourism. The synergy between agriculture and tourism isdeveloped for example through various forms such as agrotourism and ecotourism. Onesubak that embraces the concept of ecotourism but still needs to be developed is theSubak of West Intaran.This study aims to determine the potential of Subak of West Intaran and the strategies torealize the ecotourism. Data collection was conducted through in-depth interviews andquestionnaires through six key informants. Then the data were analyzed using theSWOT analysis method and IFAS & EFAS matrix analysis.The results showed that Subak of West Intaran did not fully meet the 6A ecotourismrequirements and was in one quadrant with IFAS value of (1.56) and EFAS value of(0.72) which means that West Intaran Subak is strong and has a high chance of beingdeveloped into ecotourism. Recommendations that can be given to Subak of WestIntaran, namely the government need to affirm regulations to forbid the selling ofagricultural land, support for the preservation of subak must be given to all levels ofsociety, and the establishment of an Ecotourism Management of West Intaran Subak.